Anatomical sciences at the University of Edinburgh: Initial experiences of teaching anatomy online - Alethea H.C.M. Kelsey; Victoria McCulloch; Thomas H. Gillingwater; Gordon S. Findlater; Jennifer Z. Paxton (Elsevier, 2020)
Background: The growing use of online education tools, combined with an increasing demand for anatomical education from non-traditional student cohorts, prompted us to develop a postgraduate Anatomical Sciences degree programme. Taught entirely online, this programme of study allows students from anywhere in the world to study anatomy and related subjects at the University of Edinburgh. Here, the initial three years of programme delivery is described, including an examination of the student cohorts, their geographical location, their background on application and an exploration of qualitative feedback on their programme experience. Methods: Data collected from the applications of student cohorts from academic year 2015/16 through to 2017/18 were anonymised and analysed to assess student personal characteristics. Also, qualitative student feedback data were obtained from evaluation questionnaires collected anonymously at the end of each course of the programme. Results: The majority of the Anatomical Sciences students were female (72%) and within the age range 20-29. In addition, despite being accessible all over the world, the majority of the student cohort resided in the UK (50%). Qualitative feedback suggested that online teaching in anatomy was well-received and enjoyed, particularly in the form of video lectures and bespoke online resources. Challenges such as the modes of assessment and the lack of exposure to anatomical material were noted. Conclusion: Investigating the backgrounds and opinions of the initial Anatomical Sciences students is a useful method to ensure a high level of delivery as the programme continues. Here, data and feedback for the first three years of the programme have been analysed and have highlighted specific challenges of teaching anatomy online. Finally, the future directions of online education within the anatomical sciences field is discussed. Keywords: Anatomy, Postgraduate, Online, Anatomical sciences, Education